The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fnins.2021.655901
|View full text |Cite
|
Sign up to set email alerts
|

Basal Synaptic Transmission and Long-Term Plasticity at CA3-CA1 Synapses Are Unaffected in Young Adult PINK1-Deficient Rats

Abstract: Loss of function mutations in PARK6, the gene that encodes the protein PTEN-induced kinase 1 (PINK1), cause autosomal recessive familial Parkinson’s disease (PD). While PD is clinically diagnosed by its motor symptoms, recent studies point to the impact of non-motor symptoms, including cognitive dysfunction in the early pre-motor stages of the disease (Aarsland et al., 2004; Chaudhuri and Schapira, 2009). As the hippocampus is a key structure for learning and memory, this study aimed to determine whether synap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…A study using resting-state functional MRI identified reduced connectivity between the neostriatum, midbrain dopaminergic regions, hypothalamus, and thalamus and increased connectivity between the ventral midbrain dopaminergic regions and hippocampus in 6–8-month-old PINK1 −/− rats compared to WT ( Ferris et al, 2018 ; Cai et al, 2019 ). Still, a study measuring hippocampal synaptic plasticity between 4 and 5 months old found no impairment in PINK1 −/− rats compared to controls ( Memon et al, 2021 ). Our study in this PD rat model showed elevated levels of both norepinephrine (NE) and DA in the PFC at a younger age, suggesting the possibility of abnormal DA or NE signaling therein ( Soto et al, 2024 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study using resting-state functional MRI identified reduced connectivity between the neostriatum, midbrain dopaminergic regions, hypothalamus, and thalamus and increased connectivity between the ventral midbrain dopaminergic regions and hippocampus in 6–8-month-old PINK1 −/− rats compared to WT ( Ferris et al, 2018 ; Cai et al, 2019 ). Still, a study measuring hippocampal synaptic plasticity between 4 and 5 months old found no impairment in PINK1 −/− rats compared to controls ( Memon et al, 2021 ). Our study in this PD rat model showed elevated levels of both norepinephrine (NE) and DA in the PFC at a younger age, suggesting the possibility of abnormal DA or NE signaling therein ( Soto et al, 2024 ).…”
Section: Discussionmentioning
confidence: 99%